Scientometric Analysis of Maqasid al-Shariah in Contemporary Academic Discourse - Judijanto, Loso; Ubaidillah, M. Bahtiar; Muhammadong, Muhammadong (Westscience Press, 2025)
This paper offers a thorough scientometric examination of Maqasid al-Shariah research from 2000 to 2025, utilizing data obtained from the Scopus database. The study employs performance analysis and network visualization (utilizing VOSviewer and Bibliometrix) to discern significant publication patterns, prominent authors, institutions, and nascent research themes. Findings indicate that Malaysia and Indonesia lead in worldwide maqasid research, exhibiting robust cooperation throughout Southeast Asia and the Middle East. Thematic clusters identify three primary research domains: jurisprudential foundations, Islamic finance and sustainable development, and ethical-humanistic studies. The analysis underscores a gradual transition from conventional fiqh to interdisciplinary applications, demonstrating maqasid’s flexibility in relation to modern socio-economic and technical environments. This study enhances both theoretical and practical insights into maqasid as a multifaceted framework that informs ethics, policy, and governance within contemporary Islamic philosophy.